Exploring the Significance of Bloom’s Taxonomy for Deeper Learning: A Thematic Analysis of Secondary Data - Sharma, Lok Raj (International Research Journal of MMC, 2026)
This study explores the growing relevance of Bloom’s Taxonomy as a foundational framework for promoting deeper learning in contemporary educational contexts. The objective of the study is to examine the significance of Bloom’s Taxonomy in fostering higher-order thinking skills and meaningful learning through a systematic thematic interpretation of existing knowledge. An exploratory research design was employed to gain in-depth insights into conceptual patterns and pedagogical implications associated with Bloom’s Taxonomy. The qualitative primary data consisted of words, phrases, and selected terms related to Bloom’s Taxonomy that reflect cognitive processes and learning hierarchies, while qualitative secondary data were drawn from relevant journal articles and books. The data were analyzed using thematic analysis to identify recurring concepts, cognitive domains, and instructional implications associated with deeper learning. The findings revealed that Bloom’s Taxonomy provides a structured progression from lower-order to higher-order cognitive skills, supports critical thinking, problem-solving, creativity, and reflective learning, and aligns assessment practices with learning objectives to enhance learner engagement and conceptual understanding. The findings reveal that Bloom’s Taxonomy remains a powerful and adaptable pedagogical framework for designing instruction that promotes deeper and more meaningful learning. This study will benefit teachers, curriculum designers, teacher educators, and educational researchers by guiding them in developing cognitively rich learning tasks in the future, and it benefits them at present by offering a clear theoretical and analytical understanding of how Bloom’s Taxonomy can be effectively applied to achieve deeper learning outcomes.